Urinary tract infection control in intensive care patients. Issue 38 (September 2018) - Liu, Yan; Xiao, Dong; Shi, Xiao-hui
Abstract : Abstract: This retrospective study tried to find the potential approach for reducing the urinary tract infection (UTI) in intensive care patients (ICPs) among adult population. In total, 96 eligible ICP cases were included. Of these, 48 cases received 10% povidone-iodine and were assigned to the intervention group, while the other 48 cases underwent sterile water, and were assigned to the control group for the prevention of catheter-associated UTI before indwelling urinary catheter insertion in ICP. The primary outcome was the occurrence of an UTI after the indwelling catheter. The secondary outcome was the identification of pathogenic species. The outcomes were assessed after catheter removed. After catheter removal, the occurrence of an UTI did not differ significantly between the 2 groups ( P  = .34). In addition, no significant differences regarding the pathogenic species were detected between the 2 groups ( Escherichia coli, P  = .73; Candida albicans, P  = .57; Enterococcus, P  = .65; Proteus mirabilis, P  = .50; Citrobacter, P  = .50; Klebsiella pneumoniae, P  = .57). The use of 10% povidone-iodine may not help reducing UTI in ICP.